2004
DOI: 10.4049/jimmunol.172.4.2389
|View full text |Cite
|
Sign up to set email alerts
|

Activation/Division of Lymphocytes Results in Increased Levels of Cytoplasmic Activation/Proliferation-Associated Protein-1: Prototype of a New Family of Proteins

Abstract: We purified from activated T lymphocytes a novel, highly conserved, 116-kDa, intracellular protein that occurred at high levels in the large, dividing cells of the thymus, was up-regulated when resting T or B lymphocytes or hemopoietic progenitors were activated, and was down-regulated when a monocytic leukemia, M1, was induced to differentiate. Expression of the protein was highest in the thymus and spleen and lowest in tissues with a low proportion of dividing cells such as kidney or muscle, although express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
104
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(111 citation statements)
references
References 24 publications
7
104
0
Order By: Relevance
“…Interestingly, Caprin-1 is a conserved protein exhibiting RNA binding protein properties (Grill et al, 2004). Caprin-1 is expressed in most tissue types.…”
Section: Atm and Atr Substrates Identified During Adapted Cdna Expresmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, Caprin-1 is a conserved protein exhibiting RNA binding protein properties (Grill et al, 2004). Caprin-1 is expressed in most tissue types.…”
Section: Atm and Atr Substrates Identified During Adapted Cdna Expresmentioning
confidence: 99%
“…Caprin-1 is expressed in most tissue types. Its expression is increased on entry into cell cycle and decreased on cell division completion (Grill et al, 2004). Wang et al, showed that the absence of Caprin-1 retards cell phase progression from G1 to S and defined Caprin-1 as an essential factor in normal cell proliferation (Wang et al, 2005).…”
Section: Atm and Atr Substrates Identified During Adapted Cdna Expresmentioning
confidence: 99%
See 1 more Smart Citation
“…Firstly, Caprin-1 plays an essential role in cellular proliferation. High levels of Caprin-1 have been observed in proliferating T or B lymphocytes and hemopoietic progenitors (Grill et al, 2004). At the tissue level, Caprin-1 is highly expressed in the thymus and the spleen and its level is lowest in tissues with a low proportion of dividing cells (such as kidney or muscle).…”
Section: Introductionmentioning
confidence: 99%
“…These two proteins contain two homologous regions (HR1 and HR2; Grill et al, 2004;Shiina et al, 2005; Fig. 1).…”
Section: Introductionmentioning
confidence: 99%